Empleo adecuado y gasto real per cápita mensual en la macro región selva periodo 2019-2023 - Villanueva Panaifo, Atenas Brisseth (2025)
The shortage of quality employment and inequalities in real per capita spending limit access to decent job opportunities and affect the social and economic well being of households, exacerbated by factors such as informality, inflation and insufficient public policies. Therefore, we seek to identify how adequate employment and real monthly per capita spending are presented in the Selva macro region for the period 2019-2023, considering the observational study from a quantitative approach and a descriptive non-experimental design, including as a population the quantitative data related to the variables on adequate employment and real monthly per capita spending, the research allowed to identify how adequate employment and real monthly per capita spending were presented in the Selva macro region during the period 2019 2023. The most relevant results indicate that adequate employment experienced a considerable decrease in 2020 due to the impact of the pandemic, then beginning a gradual recovery process, especially highlighting Madre de Dios, with an average of 67.46%, while Amazonas obtained the lowest percentages (35.90%). Regarding the monthly real per capita expenditure, a general negative trend is evident in almost the entire region, with a marked drop in Loreto, San Martín and Ucayali, reflecting a sustained loss in family purchasing power. Madre de Dios, despite having the highest average expenditure, also suffered significant reductions during these years.